Two Book Reviews - Howley, Craig B.; Howley, Aimee; Scribner, Kent P. (Education Policy Analysis Archives, 1994)
This issue of the Education Policy Analysis Archives comprises two book reviews: An essay review of R. G. Brown Schools of Thought by Craig Howley and Aimee Howley, and a review of Ernest R. House, Professional Evaluation by Kent P. Scribner.